Charcot-Marie-Tooth type 4B is caused by mutations in the gene encoding myotubularin-related protein-2. - Bolino, A; Muglia, M; Conforti, F; LeGuern, E; Salih, M; Georgiou, D; Christodoulou, K; Hausmanowa-Petrusewicz, I; Mandich, P; Schenone, A; Gambardella, A; Bono, F; et al. (2000)
A gene mutated in Charcot-Marie-Tooth disease type 4B (CMT4B), an autosomal recessive demyelinating neuropathy with myelin outfoldings, has been mapped on chromosome 11q22. Using a positional-cloning strategy, we identified in unrelated CMT4B patients mutations occurring in the gene MTMR2, encoding myotubularin-related protein-2, a dual specificity phosphatase (DSP).